Current issues and perspectives in nanosensors-based artificial olfactory systems for breath diagnostics and environmental exposure monitoring - Kim, Chuntae; Kang, Moon Sung; Raja, Iruthanyapandi Selestin; Oh, Jin-Woo; Joung, Yoon Ki; Han, Dong-Wook (Elsevier BV, 2024)
Artificial olfactory systems that can provide sustainable monitoring and non-invasive diagnostics are emerging for environmental exposure detection and exhaled breath diagnostics. In particular, gas-sensing platforms based on nanosensor technology show remarkable potential for integration into portable and wearable devices and are expected to become ubiquitous in our daily lives in the future. Progress in materials science has enabled nanosensors to achieve remarkable sensitivity and selectivity in gas detection. Currently, nanosensor engineering research mainly focuses on the development of artificial olfactory systems that enable multisensing and multianalysis through nanosensor arrays. This paper provides an update on nanosensor technologies and nanomaterials for gas detection, discusses the challenges faced by artificial olfactory systems, and suggests future perspectives. Furthermore, we describe the requirements for nanosensor technologies and their progress using a materials science approach. This suggested perspective highlights the importance of nanosensors for continuous environmental exposure monitoring and point-of-care testing through exhaled breath diagnostics.